Evaluation of Tax Sector Participation in Financing the Innovative Development of the Real Sector of the National Economy (Eurasian Research Bulletin, 2023)
The paper deals with the problems of tax regulation of innovation in Russia. The author examines tax incentive tools of innovation development: tax benefits of various kinds, tax credits for innovation and R&D, as well as other measures of tax support in regional economy. It is clarified that along with tax stimulus tools it is necessary to use measures disincentive in nature. The findings presented in this paper can be used in business practice as well as in educational process